Pengembangan Media Video Pembelajaran Potensi Sumber Daya Alam pada Mata Pelajaran IPS di Kelas VIII SMP - Hanafi, Fachri; Novrianti, Novrianti; Anugrah, Septriyan; Ramayanti, Elsa (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop valid and practical learning video media to be used as a supporting media in the learning process. The research was conducted using a type of research and development (R&D) with a 4D development model. The development procedures of this development are defined, design, development, and disseminate. The findings of this study, namely the development of learning video media using the Wondershare Filmora application in social studies subjects for grade VIII of junior high school, have been carried out in accordance with the development procedure that produces learning media in the form of documentary learning videos. This product has gone through the validation stage, based on the assessment of the results of material validation from teachers in the field of social studies at SMPN 8 Payakumbuh and media validation, namely Curriculum and Educational Technology lecturers. The validation results from material experts have been categorized as "Very valid" with an average of 4.7. The validation results from media expert I have been categorized as "Very Valid" with an average of 4.9 and the results from media expert II have been categorized as "Very Valid" with an average of 4.9. In the results of the practical test of learning video media products, it is at an average of 4.3 with the category "Very Practical". Based on these results, it can be concluded that the learning video media using the Wondershare filmora application in social studies subjects is declared very valid and very practical